1989
DOI: 10.1099/00221287-135-5-1061
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium Population Genetics: Genetic Variation Within and Between Populations from Diverse Locations

Abstract: Polyacrylamide gel electrophoresis (PAGE) of isoenzymes of chromosomal origin, and plasmid profile analyses, were used to investigate genetic variation within and between natural populations of Rhizobium leguminosarum biovar trifolii from diverse sources. PAGE showed that, within the biovar in general, relatively few alleles existed for the enzyme loci studied. There was a strong genetic disequilibrium between loci, suggesting that chromosomal recombination is rare. Both PAGE and plasmid profile analysis revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 20 publications
4
42
2
Order By: Relevance
“…Such complex models are not robust given the available data and were not considered further. A positive relationship has previously been observed between the number of plasmid profiles and pH (7).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Such complex models are not robust given the available data and were not considered further. A positive relationship has previously been observed between the number of plasmid profiles and pH (7).…”
Section: Resultsmentioning
confidence: 89%
“…Heavy metals have increased mobility in acidic soils and have a negative relationship with diversity (9). Decreases in diversity in acidic and metal-polluted soils have been accompanied by reductions in rhizobial density (7,9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Young et al (1987) demonstrated that, for Rhizobium leguminosarum in a pea field, each nodule was essentially an independent sample and the diversity among isolates from a single plant was almost the same as between plants across a metre, while samples 20 m apart were not significantly different. Genotype frequencies do, however, vary significantly when sites are many kilometres apart, reflecting environmental differences (Harrison et al, 1989).…”
Section: Discussionmentioning
confidence: 99%